Utilization of Coastal Resources as Livestock Areas in Konawe Islands Regency - Syamsuddin Syamsuddin; La Rianda Baka (Pascasarjana Universitas Sulawesi Tenggara, 2022)
The development of industrial-based livestock in coastal areas is an alternative in supporting domestic meat sufficiency, especially in the Konawe Islands Regency. Coastal areas have quite diverse potential in the tourism, plantation, food crop agriculture and livestock resources sectors. This study aims to analyze the potential of local feed resources based on by-products of food crops to support the development of coastal areas as livestock areas in the Konawe Islands Regency using an analysis of livestock carrying capacity based on the by-products of food crops with the data used in the form of secondary data in 2022. The results of the study showed that the carrying capacity of livestock based on by-products of food crops, namely adult cattle amounted to 1,317.64 livestock units (LU), young cattle 2,745.59 LU, and calf cattle 5,982.92 LU. The results of this study can be concluded that in order to provide animal feed throughout the year for livestock needs, it is possible to utilize local sources of feed originating from food crops.